Crushed Under Authoritarian Rule: Islam, State Power, and Religious Persecution in Tajikistan - Gabbay, Shaul M. (Advances in Social Sciences Research Journal, 2023)
This report delves into the pressing issue of human rights abuses in Tajikistan, shedding light on the authoritarian rule that governs the nation. The historical backdrop of Soviet rule and post-independence developments provide crucial context to understand the entrenched power structure. A grim picture emerges as we explore the stifling of freedom of expression and assembly, where dissent is met with repression and opposition is silenced. Media censorship and restrictions on independent journalism further erode democratic principles, leaving citizens devoid of unbiased information. Reports of torture, arbitrary detention, and a lack of due process underscore the disregard for the rule of law and the rights of individuals. This report emphasizes the importance of addressing religious persecution and the need for the international community’s involvement to encourage democratic reform and improvements in human rights, paving the way for a brighter and more inclusive future for Tajikistan.